Fertility tracking tool for visually impaired and non-visually impaired women: A qualitative study - Roselyn M. Butalid; Reynaldo M. Vequizo; Pamela F. Resurreccion (Belitung Raya Foundation, Indonesia, 2022)
Background: A natural family planning device, Fertility Tracking Tool (FTT), was developed to serve as a visual and tactile guide in monitoring the fertile and infertile days of the menstrual cycle. However, there is lack of preferences about the tool among visually impaired and non-visually impaired women. Therefore, understanding their viewpoints will provide additional input for the final design of the product. Objective: This study aimed to explore the opinions of potential users of FTT in terms of acceptability, price sensitivity, buying intention, product placement, branding, and packaging. Methods: The study employed a qualitative research design with data gathered from focus group discussions. Eleven FGD sessions were conducted participated by one group of visually impaired and ten groups of non-visually impaired women from Iligan City, Philippines, selected through purposive sampling technique. Semi-structured FGD guide was utilized, and the sessions were audio-recorded. The data were analyzed through thematic analysis. Results: The themes that emerged in the study were “adaptable” with three sub-themes (easy to use, safe to use, and aesthetic), “cost-effective”, “marketable”, “accessibility convenience”, “remarkable brand”, and “complementary packaging”. The study shows that the FTT is acceptable to both visually impaired and non-visually impaired women because it is user-friendly, has no side effects, and has a unique design. The accounts implying less price sensitivity, buying intention, accessibility preferences, notable branding, and auxiliary packaging are indications of the business potential of FTT. Conclusion: This study made a novel contribution to the nursing practice as the FTT is a newly invented device for natural family planning. The strong support from the government is necessary for FTT commercialization or even free distribution to the qualified users, not only in the research locale but extending the nationwide. The extensive FTT use may increase the natural contraceptive utilization in the Philippines, resulting in improved women’s health and population control. The FTT utilization can also be adapted across the globe to result in a better impact.